Welcome to your child's brain : how the mind grows from conception to college - Aamodt, Sandra (Bloomsbury USA, 2011)
"How children think is one of the most enduring mysteries--and difficulties--of parenthood. Martialing results from new studies and classic research, Aamodt and Wang provide the most complete answers out there on this subject and reveal new truths about everything from how to make your baby sleep, to why we love to snuggle, to how children learn, forget, play, talk, walk, and feel. Welcome to Your Child's Brain is eye-opening and necessary, soon to become a staple for parents and children alike"--